Assessment of social justice dimensions in young adults: The contribution of the belief in a just world and social dominance orientation upon its rising - Etchezahar, Edgardo; Barreiro, Alicia; Albalá Genol, Miguel Ángel; Maldonado Rico, Antonio Francisco (Frontiers in Psychology, 2022)
The aim of the study was to analyze the psychometric properties of the Social Justice Scale, composed by Representation, Recognition, and Redistribution dimensions. Likewise, the contribution of social dominance and the belief in a just world in each dimension were analyzed. A total of 471 young adults residing in Madrid participated in the online preliminary study, with an age range of 18 to 42 years with different genders (74.1% defined themselves as female). The main results indicated adequate psychometric properties for Social Justice Scale through its three dimensions. In addition, we observed that both social dominance and belief in a just world might be psychosocial variables that modulate the levels of social justice. The main findings of the research and need for replication in future studies are discussed.